PSIX-36 Effect of lauric acid based additives on piglets fecal microbiota - Sol, Cinta (J Anim Sci, 2019)
This study evaluated the effect of two feed lauric acid (LA) based additives on faecal microbiota of piglets. A total of 256 piglets were distributed (from 25 to 66d of age) in 4 treatments: CON-, diet without additives nor antibiotics; CON+, diet with Doxycycline; DIC, CON- diet plus sodium salt of coconut fatty acids distillate at 3kg/t and 1kg/t in starter and grower diets; MON, CON- diet plus monolaurine at 2.1kg/t and 0.7kg/t in starter and grower diets. The dosage of both products was made at the same level of LA (0.96kg LA/t starter and 0.32kg LA/t grower). At the end of the study, the 16S rDNA sequencing was performed. The result showed a drastic decrease in the abundance of the dominating genus Prevotella within the MON group compensated by other genera increase, mostly Selenomonadales. Streptococcus, Treponema, and unclassified Erysipelotrichaceae, Dialister or Bacillus increased their respective abundances. Treponema was more pronounced in the DIC, however, all other mentioned genera did not show a similar increase in abundance. Dialister (a marker for disease in humans) showed significantly lower abundance in DIC. In the bacterial fingerprints, a trend for clustering according to treatment was visible. Six of eight CON- samples formed a separate cluster. Six of eight samples of the DIC formed a cluster that shared very low similarity to the CON-. Four of eight CON+ samples formed a separate cluster. MON samples were interspersed among all samples and showed no distinct clustering. Even though quantitative microbial comparisons were only anecdotal, observations may indicate a more “healthier” microbiota in the DIC than was present in the MON. DIC also showed a much closer similarity of bacterial fingerprints for the pooled samples in the qualitative analysis indicating that DIC had a higher potential to modify the faecal (hindgut) microbiota than MON.